Inverse of the distance matrix of a bi-block graph. Issue 8 (2nd August 2016) - Hou, Yaoping; Sun, Yajing
Abstract : A connected graph, all of whose blocks are complete bipartite graphs (of possibly varying sizes) is called bi-block graph. Let be the distance matrix of . If is not a block of then is nonsingular. In this paper, we give formulas for both the determinant and inverse of .